Synthesis and anti-tumor activity evaluation of salinomycin C20-O-alkyl/benzyl oxime derivatives. Issue 4 (10th January 2022) - Li, Bo; Wu, Jun; Tang, Lei; Lian, Xu; Li, Zhongwen; Duan, Wenfang; Qin, Tong; Zhao, Xintong; Hu, Yuhua; Zhang, Chi; Li, Tianlei; Hao, Jie; et al.
Abstract : Seventeen C20- O -alkyl/benzyl oxime derivatives were synthesized by a concise and effective method, which showed 15 240 folds better antiproliferative activity, more potent ion binding and transport ability and better selectivity indexes (SI) than salinomycin. Abstract : Seventeen C20- O -alkyl/benzyl oxime derivatives were synthesized by a concise and effective method. Most of these derivatives showed tens to several hundred nanomolar IC50 values against HT-29 colorectal, HGC-27 gastric and MDA-MB-231 breast cancer cells, whose antiproliferative activity is 15–240 fold better than that of salinomycin. The C20-oxime etherified derivatives can coordinate potassium ions, and further adjust the cytosolic Ca 2+ concentrations in HT-29 cells. The significant improvement of the potency should be attributed to the better ion binding and transport ability of the modified derivatives. In addition, the C20- O -alkyl/benzyl oxime derivatives showed much better selectivity indexes (SI) than salinomycin, indicating that they present lower neurotoxic risk.